Focusing on the role of secretin/adhesion (Class B) G protein-coupled receptors in placental development and preeclampsia - Yin, Aiqi; Guan, Xiaonian; Zhang, Jian V.; Niu, Jianmin (Frontiers in Cell and Developmental Biology, 2022)
Preeclampsia, a clinical syndrome mainly characterized by hypertension and proteinuria, with a worldwide incidence of 3–8% and high maternal mortality, is a risk factor highly associated with maternal and offspring cardiovascular disease. However, the etiology and pathogenesis of preeclampsia are complicated and have not been fully elucidated. Obesity, immunological diseases and endocrine metabolic diseases are high-risk factors for the development of preeclampsia. Effective methods to treat preeclampsia are lacking, and termination of pregnancy remains the only curative treatment for preeclampsia. The pathogenesis of preeclampsia include poor placentation, uteroplacental malperfusion, oxidative stress, endoplasmic reticulum stress, dysregulated immune tolerance, vascular inflammation and endothelial cell dysfunction. The notion that placenta is the core factor in the pathogenesis of preeclampsia is still prevailing. G protein-coupled receptors, the largest family of membrane proteins in eukaryotes and the largest drug target family to date, exhibit diversity in structure and function. Among them, the secretin/adhesion (Class B) G protein-coupled receptors are essential drug targets for human diseases, such as endocrine diseases and cardiometabolic diseases. Given the great value of the secretin/adhesion (Class B) G protein-coupled receptors in the regulation of cardiovascular system function and the drug target exploration, we summarize the role of these receptors in placental development and preeclampsia, and outlined the relevant pathological mechanisms, thereby providing potential drug targets for preeclampsia treatment.